An effectiveness distribution channel in improving profitability and sales toward Delima Oil Products Sdn Bhd / Norasikin Yahaya - Yahaya, Norasikin (Faculty of Business and Management, 2007)
Delima Oil Products Sdn. Bhd is the largest Palm Oil Producer in the world. It has a monopoly on the palm oil and has a considerable market share of palm oils market in domestic and international industry. Basically, the research objectives of this study are to identify the effectiveness distribution channel toward Delima Oil Product Sdn.Bhd to deliver their services to consumers where it need to focus not just on understanding product choice, but also on understanding the reasons for channel choice. The effectiveness distributions channels are an importance issues that need to be reviewed in improve DOPSB profitability and sales.